Research Trends on the Use of Avocado Starch for Biofilm Production: Bibliometric Analysis Using VOSviewer - Nazir, Novizar; Hariry, Amelia; Widiyastuti, W.; Panatarani , Camelia; Praseptiangga, Danar; Aziz, Rizki; Syamani, Firda Aulya (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Avocado starch has gained attention as a potential bio-based material due to its unique features that make it suitable for forming biofilms. This work thoroughly examines the changing field of research focused on using avocado starch for biofilm applications. It uses VOSviewer, a tool for analyzing bibliometric data, to uncover important insights using a database of Scopus-indexed journal publishers. This study aimed to determine research trends on the use of avocado starch for biofilm production. The Scopus database collected information on research trends in the use of avocado starch for biofilm production. To obtain search results, subject categories with titles, keywords, and abstract criteria from the use of avocado starch extraction, biofilm/bioplastic production, and biocomposite were used as a reference. Using VOSviewer, search result extraction was performed. The results of bibliometric mapping were then further evaluated. The findings of the bibliometric study are demonstrated through network visualization, overlay visualization, and density visualization. The findings indicate that starch produced from avocados has the potential to be a viable resource for manufacturing biofilms. However, further investigation is required to enhance the overall quality of the produced biofilm.